Effect of the Microstructure of the Functional Layers on the Efficiency of Perovskite Solar Cells. Issue 20 (22nd February 2017) - Huang, Fuzhi; Pascoe, Alexander R.; Wu, Wu‐Qiang; Ku, Zhiliang; Peng, Yong; Zhong, Jie; Caruso, Rachel A.; Cheng, Yi‐Bing
Abstract : The efficiencies of the hybrid organic–inorganic perovskite solar cells have been rapidly approaching the benchmarks held by the leading thin‐film photovoltaic technologies. Arguably, one of the most important factors leading to this rapid advancement is the ability to manipulate the microstructure of the perovskite layer and the adjacent functional layers within the device. Here, an analysis of the nucleation and growth models relevant to the formation of perovskite films is provided, along with the effect of the perovskite microstructure (grain sizes and voids) on device performance. In addition, the effect of a compact or mesoporous electron‐transport‐layer (ETL) microstructure on the perovskite film formation and the optical/photoelectric properties at the ETL/perovskite interface are overviewed. Insight into the formation of the functional layers within a perovskite solar cell is provided, and potential avenues for further development of the perovskite microstructure are identified. Abstract : The performance of perovskite solar cells is greatly affected by the microstructure of the functional layers, especially that of the perovskite film. By controlling the nucleation and crystal growth process, desirable microstructures (grains and voids size) of the perovskite films, such as dense films with large grains, can be achieved for high‐efficiency solar cells.